Heating and cooling performance analysis of a ground source heat pump system in Southern Germany. (January 2015) - Luo, Jin; Rohn, Joachim; Bayer, Manfred; Priess, Anna; Wilkmann, Lucas; Xiang, Wei
Highlights: We examine heating and cooling performance of a GSHP system. Similar thermal performance of the BHEs with three different borehole diameters. COP of the GSHP system is estimated to be 3.9 for a typical winter day. EER of the GSHP system is assessed to be 8.0 for a typical summer day. SEER increases along the years, whereas seasonal COP decreases at the same period. Abstract: This paper examines thermal performance of a ground source heat pump (GSHP) system. The GSHP system was installed in an office building in Nuremberg city of Germany. In order to evaluate system performance the GSHP system has been continuously monitored for 4 years. Heating and cooling performance of the GSHP system is analyzed based on the accumulated data. Major findings of this work include: (1) coefficient of performance (COP) is estimated to be 3.9 for a typical winter day and energy efficiency ratio (EER) is assessed to be 8.0 for a typical summer day. These results indicate that the GSHP system has a higher efficiency for building cooling than building heating. (2) For a long-term period, the seasonal energy efficiency ratio (SEER) of the GSHP system is observed to increase by 8.7% annually, whereas the seasonal COP is decreased by 4.0% over a 4-year period. The heating and cooling performance of the GSHP system migrates in opposite trend is caused by the unevenly distributed heating and cooling load of the building. This phenomenon deserves serious attention in the design of future GSHP systems in order to avoid the reducing of energy efficiency over long-term operation.